Combined Use of ECMO, Prone Positioning, and APRV in the Management of Severe COVID-19 Patients - Stephanie L Ong; Hossam Tantawy; Roland Assi; Astha Chichra; Miriam M Treggiari (Clinical Medicine Insights: Circulatory, Respiratory and Pulmonary Medicine, 2022)
Background Severe COVID-19-associated Acute Respiratory Distress Syndrome (ARDS) may warrant extracorporeal membrane oxygenation (ECMO). We evaluated the safety and physiologic changes in oxygenation and hemodynamic profile during ECMO, prone positioning, and the two modalities combined in patients receiving veno-venous (VV) ECMO. Methods Cohort study of consecutive adult patients with COVID-19-associated ARDS requiring VV-ECMO, classified into three groups: ECMO support only; Prone positioning only; and Prone positioning during ECMO. We collected hemodynamic, respiratory and ventilation variables as follows: pre-treatment, 1, 6, and 24 h post-treatment, and documented treatment-related complications. On-treatment variables were compared with pre-treatment using one-sample paired t-test with Bonferroni correction. Results Fourteen patients (mean age 48.1 [SD 9.3] years, male [100%]) received VV-ECMO. Of those, 10 patients had data during prone positioning alone and seven had data while proned on ECMO. While on ECMO, patients had improvement in oxygen saturation, PaO 2 /FiO 2 ratio, and minute ventilation up to 24 h post-treatment. Vasopressor requirements increased with ECMO at 1 h and 24 h post-treatment. Prone positioning was not associated with clinically significant hemodynamic or respiratory changes, either alone or during ECMO support. All patients sustained deep tissue injuries, but only those on the face or chest were related to prone positioning. Three patients required cannula replacement. In-hospital mortality was 43%. Conclusions VV-ECMO and prone positioning in patients with COVID-19 ARDS was overall well-tolerated; however, physiologic improvements were marginal, and patients sustained deep tissue injuries. Although this was a selected population with high mortality, our data call into question the benefits of these management modalities in this severe COVID-19 population.